Synthesis and application of nonisocyanate polyurethanes - Figovsky, Oleg; Shapovalov, Leonid; Leykin, Alexander (Publishing House of Lviv Polytechnic National University, 2016)
The latest published achievements in the research and developments of non-isocyanate polyurethanes on the base of five-membered cyclic carbonates and amines are briefly presented. Preparations of hybrid epoxy-amine hydroxyurethane-grafted polymers with a controlled number of cross-links are described. Examples of the use of hydroxyurethanes of different nature for modification of the oligomeric compositions are also given. Представлені останні опубліковані досягнення в області досліджень і розробок неізоціанатних поліуретанів на основі п'ятичленних циклічних карбонатів і амінів. Описано приготування гібридних епокси-амінних гідроксиуретан-прищеплених полімерів з контрольованою кількістю зшивок. Наведено приклади використання гідроксиуретанів різної природи для модифікації олігомерних композицій.
Синтез і застосування неізоціанатних поліуретанів
Keywords: non-isocyanate polyurethanes; hybrid hydroxyurethane-grafted polymers; неізоціанатні поліуретани; гібридні гідроксиуретан-прищеплені полімери